(untitled) (Research, Society and Development, 2019)
Discussions in search of new methodologies that make the teaching of mathematics more attractive and meaningful has been incessant, were conducted research in the area of mathematics education that taught mathematics (content) in the classroom as well as the form (methodology) as being taught did not correspond to the needs of the student for the formation of citizenship as social beings. Thus, the purpose of this article is to point out methodological references and to establish some steps for the work with the modeling in the mathematical contents in the classroom. The Mathematical Modelling is a significant tool in the process, since it deals with an alternative methodology for Mathematics teaching. Teachers can use this methodology in both elementary and high school, aims to interpret and understand the most diverse phenomena of our daily life, the modeling provides the facilitation of learning by the applications of mathematical concepts making mathematical content more meaningful, from abstract to concrete. In this context, we sought to analyze the ways that modeling can provide to do mathematics in school and within the classroom, seeking to improve the quality of teaching and learning in the process of teaching and learning. In this sense, this work presents several aspects favored by Mathematical Modeling as a methodological alternative for the teaching of Mathematics, mainly in Basic Education. It points out the methodological orientations and establishes some steps for the work with the modeling in the mathematical contents in the classroom.